Arterial Stiffness in Inflammatory Bowel Disease: An Updated Systematic Review and Meta-Analysis - Qiongqiong Lu,; Qiongqiong Lu,; Rui Shi,; Tangyou Mao,; Zhibin Wang,; Zhongmei Sun,; Xiang Tan,; Yi Wang,; Junxiang Li, (Turkish Journal of Gastroenterology, 2021)
Background: This systematic review and meta-analysis were carried out on well-conducted and adequately powered studies to explore whether arterial stiffness was associated with inflammatory bowel disease (IBD). Methods: The search for potential literature was conducted on PubMed, MEDLINE, Cochrane Library, and Embase from inception to February 15, 2020. The studies assessing arterial stiffness in IBD were reviewed and included. Results: Conclusively, 17 eligible trials with a total of 2188 participants were in compliance with the inclusion criteria. Of the included 2188 participants, the cases for ulcerative colitis (UC) and Crohn’s disease (CD) were 558 and 693, respectively. Altogether 10 studies were conducted to evaluate the carotid-femoral pulse wave velocity (CPWV) in overall IBD patients, which was significantly increased with the mean difference (MD) and 95% CI as 0.70 (0.48-0.92, P < .01). The pooled results for CPWV in patients with CD and UC were also faster than that of control groups with MD and 95% CI as 1.09 (0.45-1.72) and 0.57 (0.57-1.24), respectively. The CPWV in CD and UC groups was comparable with a MD of 0.07 (P = .74, 95% CI: −0.32 to 0.45). Conclusion: Arterial stiffness had associations with the overall IBD, UC, and CD with a similar strength of association between UC and CD. Cite this article as: Lu Q, Shi R, Mao T, et al. Arterial stiffness in inflammatory bowel disease: An updated systematic review and meta-analysis. Turk J Gastroenterol. 2021; 32(5): 422-430.